MODEL ELITE WORLD JUNIOR HANDBALL GOALKEEPER WITH VISUALIZATION - Sanja Bajgorić; Muris Đug; Nina Bijedić (Sport Scientific And Practical Aspects, 2025)
The aim of this research is to construct the model of an elite world junior handball goalkeeper, based on the information from the official statistics run by the EHF at the 2013 World Junior Championship in Bosnia and Herzegovina. In total, 42 elite world junior goalkeepers were analysed. The model of the elite world junior handball player was constructed on the basis of a set of 28 variables: The basic central and dispersion parameters, factor, discriminatory and regression analysis were calculated for all examined variables. To determine the model goalkeeper, the average values of tengoalkeepers were taken by each of the selected defence elements, which resulted in average results of the best and at the same time reduced variability was achieved. On the basis of the results, a model of the elite world junior goalkeeper was constructed, who should, on average, be 189 cm high, weigh 88.56 kg and have a BMI of 24.71. The goalkeeper, as a model, should have 48% to 52.78% of defences from the field. From the line, this number shouldbe 32.00% to 50.41%, while from the wing he should have from 28.69% to 46.18% defence. From the passage,he should have a percentage of defence from 29.87% to 48.01%, while the high-speed centre should have a percentage of defence from 34.07% to 53.20%. From the seven meterline he should have from 36.42% to 46.56% defence percentage. Total should be from 44.71% to 53.20% of defence per game.